„Il calcio è una metafora della vita” (Jean Paul Sartre). Metafora nel linguaggio della cronaca di calcio italiana nei quotidiani a stampa e on line - Szemberska, Anna (Studia Romanica Posnaniensia, 2009)
The objective of this article is a thorough analysis of a particular form of communication which is constituted by the language of football journalism. As we demonstrate in the present paper, the language of Italian football press is a rich source not only of loanwords, but also and mainly of rhetorical figures, especially metaphors. Besides the undeniable ubiquity of figurativeness, another phenomenon analysed in the article are semantic areas present in such a press, which variety and multiple aspects are considered in our specific study. Finally, our description of the language of Italian football journalism proves that these are not only linguistic considerations, but also cultural and multimedia.